The beneficial effects of social collaboration on episodic memory in children: insights from ongoing and post-collaborative recognition. - Nie, Aiqing; Tang, Liang; Wang, Qiao (Journal of General Psychology)
Previous research on adults has indicated that social collaboration can have both detrimental and beneficial effects on episodic memory. These effects include collaborative inhibition, error pruning, and post-collaborative memory benefit. However, most studies have focused on adults using the collaborative recall method, with limited research specifically examining children. The current study aimed to investigate the impact of social collaboration on episodic memory in 9–10-year-old children through the collaborative recognition method. The experiment included three main phases: encoding, collaborative recognition, and post-collaborative recognition. Age-stereotypical actions were used as the experimental materials. During the collaborative-recognition phase, participants were divided into collaborative and nominal groups, while they worked independently in other phases. Both test phases included tasks that focused on item memory for recognizing actions and source memory for identifying the protagonists performing the actions. Significant collaborative facilitation was recorded during the collaborative recognition phase, before and after the influence of guessing was removed. Furthermore, the post-collaborative recognition phase displayed a post-collaborative memory benefit. The error pruning was observed across both recognition phases. These effects were regulated by stereotype consistency. In summary, unlike previous studies that found both detrimental and beneficial effects in adults, this study revealed the significant beneficial impact of collaborative recognition on children's episodic memory. We discussed the results from various perspectives and theories, and introduced a new theory called the retrieval strategy tradeoff hypothesis to consider additional possibilities. Moving forward, we suggest several directions for future research.